Regional goals and objectives of the establishment of special economic zones - Ergashev Olim, (THE INNOVATION ECONOMY, 2026)
This article presents scientifically based proposals and recommendations on the processes of socio economic development of regions by attracting local and foreign investments on the main goals and tasks of the establishment of special economic zones. Also, issues aimed at improving the methodical provision of implementation and substantiation of the goals and main features of the establishment of a special economic zone in the regions are highlighted.